Major depressive disorder in post-secondary students attending foodbanks in France - Rambliere, Lison; Leservoisier, Clémentine; Bedo, Ysé; Macalli, Melissa; Lebugle, Amandine; Douay, Caroline; Guénée, Lorraine (Frontiers in Public Health, 2023)
Introduction Poor mental health among youth is a major public health issue that has risen to the forefront since the COVID-19 crisis, especially among post-secondary students and precarious populations. The objectives of this work were to evaluate the rate of major depressive disorder (MDD) among precarious post-secondary students in the greater Paris region, to describe its risk factors, and to identify determinants for not seeking care. Methods We conducted a multi-site, cross-sectional survey of post-secondary students attending a selection of 13 student foodbanks in the greater Paris region (France) between 30 November 2021 and 27 January 2022. This study had two complementary epidemiological and sociological components: a quantitative description of MDD through completion of a questionnaire performed through face-to-face or telephone interviews, and a qualitative assessment of the factors underlying MDD through in-depth follow-up interviews conducted among a sub-selection of students who participated in the first phase. Results Among 456 students who participated in our survey, 35.7% presented with MDD. The risk of suffering from MDD was higher among women, students housed by third-parties, students reporting moderately to severely hungry and/or poor physical health. Students receiving material and/or social support were less likely to present with MDD. Among students who reported needing health care in the last year or since their arrival in France, 51.4% did not seek care. Conclusion To address poor mental health among precarious students, policy action must jointly consider financial precarity, administrative barriers, housing, food security, physical health, and access to health services, especially mental health.